2020
DOI: 10.1371/journal.pone.0237171
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the adapted measles vaccine hesitancy scale in Sudan

Abstract: Background There is a need for reliable and validated tools to identify, classify, and quantify vaccine-hesitancy in low and middle-income countries, such as Sudan. We evaluated the psychometric properties of an adapted version of the measles vaccine hesitancy scale by assessing its reliability, convergent validity, and criterion validity in Sudan. The vaccine hesitancy scale (VHS) was originally developed by the WHO/SAGE Working Group of Vaccine Hesitancy. Methods A community-based survey among parents was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 24 publications
0
21
0
1
Order By: Relevance
“…Similarly, we found that the 9-item version showed the best goodness of fit. Many studies also found that CFA complies well [16,18,37].…”
Section: Model) As Seen In Tablementioning
confidence: 84%
See 3 more Smart Citations
“…Similarly, we found that the 9-item version showed the best goodness of fit. Many studies also found that CFA complies well [16,18,37].…”
Section: Model) As Seen In Tablementioning
confidence: 84%
“…Also, Luyten et al [37] used the English version and determined that the scale consisting of two factors and 9 items explained 71.8% of the total variance . Sabahelzain et al [18] observed that the two-factor structure of the 10-item version of the scale made up 50.8% of the total variance in the study of adapting the scale to the Saudi language. This study was found that the scale consisting of two factors and a total of 9 items constituted 68.69% of the total variance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ölçeğinin Türkçe Geçerlik Ve Güvenirliği 502 Tortop, 2020;Çevik vd., 2019;Domek et al, 2018;Larson, 2015;Opel et al, 2011;Roberts et al 2015;Shaheera et al, 2017) veya enflüanza (Streltz et al, 2015, HPV (McRee et al, 2010;Sunar ve Süt, 2019), kızamık (Sabahelzain, 2020) veya genel çocukluk çağı aşıları (Napolitano et al, 2018;Shapiro et al, 2018;Önal et al, 2021) gibi belli aşılara özgüdür. Ayrıca SAGE Aşı Grubunun ölçüm aracı ABD (Kempe et al, 2020), Romanya Guatemala, Etiyopya (Wagner et al, 2019, (Miko et al, 2019), Çin (Ren et al, 2018), Fransa (Bacquier et al, 2018 gibi birçok farklı kültür ve ülkedeki ebeveynlere uygulanmıştır.…”
Section: Aşı Tereddüdüunclassified